БОШЛАНҒИЧ ТАЪЛИМДА МАТННИ ТАҲЛИЛ ҚИЛИШ МЕТОДИ САМАРАДОРЛИГИНИ БАҲОЛАШ - Атаджанов, Х.Л.; Абдуразакова, Н.С. (SCIENCE and SOCIETY, 2025)
The article provides information on applying the text analysis method in reading literacy lessons and assessing the effectiveness of the text analysis method in primary education.